Dewan Bandaraya Kuala Lumpur / Muhammad Afif Abu Talib - Abu Talib, Muhammad Afif (Faculty Of Civil Engineering, 2019)
The purposes of written this report is to explain about the Industrial Training. The scope of study is engineering and the various environments at Jabatan Kejuruteraan Awam Dan Pengangkutan Bandar. The importance of internship is to give exposure to the students the real situation in engineering professions. Besides, it also can build and increase positive and critical thinking when overcoming engineering problems with the suitable and rational solution. Jabatan Kejuruteraan Awam Dan Pengangkutan Bandar responsible for the road in Kuala Lumpur and the DBKL project. Every road closure, maintenance of the road and transportation including construction project will be handle by JKAPB. At JKAPB, the entire applicants for road closure need to submit their form to this department for the approval. If the applicants close the road without getting the approval, Jabatan Penguatkuasa will fine them. This seems small issue, but it is important to ensure everybody comforts and to avoid any complain from the road users. Furthermore, JKAPB also does open tender for road marking after prepared the Bill of Quantities. After that, all of the tender will be process and the contractor will be picked based on their experience with the infrastructure works. Last but not least, during the Industrial Training, students are well exposed to the real working environment and challenges in many natures of works such as in JKAPB. Through many situations and problems encountered, the students can obtained a lot of new inputs and skills which is useful under the guidance of experienced people.